A newly discovered linkage between proteoglycans and hair biology: decorin acts as an anagen inducer. Issue 8 (August 2014) - Inui, Shigeki; Itami, Satoshi
Abstract Proteoglycans have been suggested to play pivotal roles in hair biology. Decorin is a prototypical member of the small leucine‐rich proteoglycan family, which is involved in numerous biological processes. However, the role of decorin in the hair cycle has not been elucidated. Moreover, the effects of decorin on the activities of many growth factors are complex, and it is hard to predict whether decorin would affect hair growth or the hair cycle positively or negatively. Jing et al. focused on the potential role of decorin in the hair cycle and found that decorin is highly expressed in the epidermis, in hair follicle epithelial cells and in dermal papilla cells in the anagen phase. The expression of decorin was decreased during catagen to telogen, except for the bulge region. Exogenous administration of decorin accelerated anagen and delayed catagen transition as a positive regulator of the hair cycle. Because TGF‐β is one of the androgen‐induced pathogenic factors in androgenetic alopecia, this study provides clues to understand the pathogenesis and new therapeutic targets of hair loss.